ROAD HOUSE - Henry, David Lee; Henkin, Hilary; Swayze, Patrick; Gazzara, Ben, 1930-2012; Lynch, Kelly, 1959-; Tighe, Kevin, 1944-; David, Keith; Wilhoite, Kathleen, 1964-; Elliott, Sam, 1944-; Cundey, Dean, 1945-; Kamen, Michael (Twentieth Century Fox Home Entertainment, 2015)
A legendary bouncer comes to Jasper, Missouri, for a special purpose: to restore order at the notorious Double Deuce bar. In one spectacular fight after another, Dalton rids the bar of thugs and henchmen. But when he runs afoul of a ruthless crime boss, the stage is set for a blistering showdown that will leave only one man standing.